96. Increasing adoption of precision agriculture via gamification: the farming simulator case - Pavlenko, T.; Paraforos, D.S.; Fenrich, D.; Braun, S.; Murdoch, A.; Tranter, R.; Gadanakis, Yiorgos; Arnoult, M.; Engel, T. (My University, 2021)
Even though precision farming (PF) technologies offer apparent on-farm and off-farm benefits, their adoption remains low. A lot of efforts are put towards increasing interest among farmers and other actors and motivating them to use PF techniques. Among others, gamification is a popular method that is being increasingly used not only in agriculture but in many other disciplines. This study describes the implementation of PF principles as an added application (mod) in a farming simulator game. The developed mod includes several new features: RTK base stations, soil types, soil sampling, pH value, site-specific variable rate lime and nitrogen application, yield mapping and economic analysis.
Keywords: Precision Farming; Gamification; Agriculture; EIT Food